2018
DOI: 10.3390/rs10020230
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Arctic Sea Ice Extent Trends and Statistical Projections Using Satellite Data

Abstract: An ice-free Arctic summer would have pronounced impacts on global climate, coastal habitats, national security, and the shipping industry. Rapid and accelerated Arctic sea ice loss has placed the reality of an ice-free Arctic summer even closer to the present day. Accurate projection of the first Arctic ice-free summer year is extremely important for business planning and climate change mitigation, but the projection can be affected by many factors. Using an inter-calibrated satellite sea ice product, this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
0
13
2
Order By: Relevance
“…Dev. In comparison to the similar study done by Peng et al (2018), where a 15% threshold was used, the models calibrated with the full time series and the last 30 year time periods result in FIASY estimates that are slightly later and with smaller spreads in this analysis. The difference in this paper is that the full time series is 1979-2017, rather than 1979-2015, and the last 30 years is 1988-2017, rather than 1986-2015.…”
Section: Yearsmentioning
confidence: 85%
See 1 more Smart Citation
“…Dev. In comparison to the similar study done by Peng et al (2018), where a 15% threshold was used, the models calibrated with the full time series and the last 30 year time periods result in FIASY estimates that are slightly later and with smaller spreads in this analysis. The difference in this paper is that the full time series is 1979-2017, rather than 1979-2015, and the last 30 years is 1988-2017, rather than 1986-2015.…”
Section: Yearsmentioning
confidence: 85%
“…Similar to the analysis done in Peng et al (2018), where a threshold choice of 15% was used, we perform statistical model calibration and selection with data from SIE annual minimums derived from differing thresholds to determine the impact of threshold choice on optimal model selection along with the FIASY [19]. Using an updated version of the same long-term, consistent time series of sea ice data, we compare six commonly used statistical models for this type of application.…”
Section: Statistical Model Fitting and Selection Using Sie Data With mentioning
confidence: 99%
“…Rapid and accelerated Arctic sea ice loss has brought the possibility of a nearly ice-free Arctic summer well into our near future (e.g., [1][2][3][4]). An Arctic ice-free state is defined as when the total Arctic sea ice extent (SIE) falls below one million square kilometers (10 6 km 2 ) [1].…”
Section: Introductionmentioning
confidence: 99%
“…By using sea ice extent predictions from six statistical models that were curve-fitted with satellite observational data from 1979-2015, Peng et al [4] demonstrated that the predicted FIASYs are converging around the year 2037, with a margin of error of seven years and with the earliest FIASY predicted to be in 2031. A similar conclusion was obtained by Wang and Overland [1,2], who used a subset of coupled climate models that participated in the Coupled Model Intercomparison Project (CMIP) Phase 3 and Phase 5 (CMIP3 and CMIP5, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation